2008
DOI: 10.1590/s0006-87052008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e produtividade de algodoeiro submetido a cloreto de mepiquat e doses de nitrogênio

Abstract: Em regiões com condições climáticas favoráveis como de cerrado, tem-se verificado excessivo crescimento vegetativo do algodoeiro, principalmente quando associado à utilização de elevadas doses de N, justificando a utilização de substâncias reguladoras de crescimento para obtenção de plantas mais produtivas e com porte adequado à colheita mecanizada. Neste trabalho, objetivou-se avaliar o crescimento e a produtividade do algodoeiro cv. FMX 986, submetido às doses de N e cloreto de mepiquat, nas condições edafoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 6 publications
6
11
0
9
Order By: Relevance
“…These results are consistent with those found by Teixeira;Kikuti and Borém (2008), that using different nitrogen doses combined with the use of growth regulators, did not find differences in plant height at 90 d.a.e., for the doses studied. The results show that as the N doses applied were increased, the cotton plant heights increased, with 1.24 m representing the highest measure found for the highest dose applied (90 kg N ha -1 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with those found by Teixeira;Kikuti and Borém (2008), that using different nitrogen doses combined with the use of growth regulators, did not find differences in plant height at 90 d.a.e., for the doses studied. The results show that as the N doses applied were increased, the cotton plant heights increased, with 1.24 m representing the highest measure found for the highest dose applied (90 kg N ha -1 ).…”
Section: Resultssupporting
confidence: 93%
“…The variation between the maximum dose applied, and the absence of fertilization reached 678.52 kg ha -1 . These results agree with those found by Teixeira, Kikuti and Borém (2008) that when using increased doses of N applied in equal doses to the sowing and to the covers, found maximum s (3633 kg ha -1 ) when using 131 kg N ha -1 , when compared to the control group (3362 kg ha -1 ). The results found by Lamas and Staut (2005), corroborate this report, when they had a significant effect on the cotton by the addition of up to 150 kg N ha -1 .…”
Section: Y=2231supporting
confidence: 92%
“…In accordance with these results, Teixeira et al (2008), when studying the effects of increasing doses of ammonium sulfate and urea on cotton yields, observed a maximum yield (3,633 kg ha -1 ) with 131 kg ha -1 of N applied in equal doses broadcasted at sowing compared to the control (3,362 kg ha -1 ). Additionally, Lamas and Staut (2005) …”
Section: Resultssupporting
confidence: 76%
“…Athayde and Lamas (1999) also reported a decrease in cotton height and a result similar to that of Zhao and Oosterhuis (2000) was observed until 21 days after sowing even though MC was sprayed on cotton leaves rather than seeds, as in the present study. Teixeira et al (2008) also reported significant differences in cotton plant height, cultivar FMX 986, when MC was used in the leaves, and according to the authors, this effect could be attributed to the anti-gibberellin effect of the product. Yeates et al (2005) also observed shorter plant when the seed surfaces were treated with MC.…”
Section: Resultsmentioning
confidence: 89%